A Comparison of Psychiatric Rating Scales for the Assessment of Anxiety and Depression in ESRD Patients - Osama Habib, Azhar Ali Khan, Maryam Javed, Sameer Sattar, Sehrish Sarwar, Ayesha Jamil (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Depression and anxiety are among the most comorbid disorders in End stage renal disease (ESRD) patients. Most of the scales currently in use for screening of anxiety and depression are translated into Urdu language from English. Aga khan university anxiety and depression scales (AKUADS) ,a scale developed in Urdu language contains items that assess for psychological as well as somatic symptoms of anxiety and depression. The aim of the current study was to compare the AKUADS with two other commonly used scales for the detection of anxiety and depression in ESRD patients Materials and methods: Current inpatients at Nephrology unit, Sheikh Zayed Hospital, Lahore who were on dialysis were invited to take part in the study. Patients who provided informed written consent were administered three psychiatric rating scales: AKUADS, patient health questionnaire 9 (PHQ-9) for assessment of depression and General anxiety disorder 7 (GAD-7) for assessment of anxiety. Results: AKUADS was strongly related to both GAD-7 and PHQ-9. The prevalence rate of depression in our patients was 36.4% (Mild depression) as assessed by PHQ-9 and of anxiety was 24.6% as assessed by GAD-7. The prevalence of anxiety and depression as assessed by AKUADS was 33%. Female participants were significantly more likely to have higher scores on all the three scales as compared to male patients Conclusions: AKUADS can be used for the screening of anxiety and depressive disorders in the local population and is well correlated with other more widely used and well validated psychiatric rating scales.